Body Mass Index Does Not Affect Response to Rituximab in Patients with Rheumatoid Arthritis: Results from Turkbio Registry - Koca, Suleyman Serdar; Karatas, Ahmet; Oz, Burak; Dalkilic, Ediz; Can, Gercek; Pehlivan, Yavuz; Onen, Fatos (Wiley, 2017)
[Abstract Not Available]
81st Annual Meeting of the American-College-of-Rheumatology (ACR) / Association-of-Rheumatology-Health-Professionals (ARHP) -- NOV 03-08, 2017 -- San Diego, CA